The rare reason of pain in hip girdle: Mucolipidosis type 3 gamma - Kolkıran, Abdulkerim; Karaosmanoğlu, Beren; Taşkıran, Zihni Ekim; Şimşek-Kiper, Pelin Özlem; Utine, Gülen Eda (The Turkish Journal of Pediatrics, 2021)
Background. Mucolipidosis type 3 gamma (ML-IIIγ) is an autosomal recessive, rare and slowly progressive lysosomal storage disease. Short stature, restricted joint mobility, thick skin, and flat face with mildly coarse features are major clinical findings. It usually manifests in the third year. With advancing age, claw hand deformities, carpal tunnel syndrome, and scoliosis may develop. Morbidity is determined mainly by skeletal involvement. N-acetyl glucosamine-1 phospotransferase enzyme is composed of 2α, 2β and 2γ subunits. The active enzyme is essential in the transport of hydrolases to the lysosomes, via addition of mannose-6-phosphate in the Golgi apparatus. GNPTG gene encodes the γ2 subunits, and biallelic mutations cause ML-IIIγ. Case. A previously healthy 14-year-old male patient had leg pain after the age of nine, and was admitted with short stature, mild coarse face, pectus deformity, digital stiffness, scoliosis, genu valgum and mitral valve prolapse. He did not have intellectual disability or corneal clouding. Radiographs showed irregularities in the acetabular roof and proximal epiphyses of the femur and irregularities in the end plates of vertebral bodies. A novel homozygous missense variant in the exon 5 of GNPTG, c.316G > T, confirmed the diagnosis of ML- IIIγ. Juvenile idiopathic arthritis (JIA), progressive pseudorheumatoid dysplasia (PPRD), ML-II, ML-IIIαβ, galactosialidosis and mucopolysaccharidosis should be considered in the differential diagnosis. Conclusions. ML-IIIγ should be kept in mind in populations with high consanguineous marriage rates or with possible founder effect, in patients with short stature and skeletal destruction. Genetic tests should be planned for a definitive diagnosis.